2007
DOI: 10.1111/j.1365-2591.2007.01322.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of primary root canal treatment: systematic review of the literature – Part 1. Effects of study characteristics on probability of success

Abstract: The estimated weighted pooled success rates of treatments completed at least 1 year prior to review, ranged between 68% and 85% when strict criteria were used. The reported success rates had not improved over the last four (or five) decades. The quality of evidence for treatment factors affecting primary root canal treatment outcome is sub-optimal; there was substantial variation in the study-designs. It would be desirable to standardize aspects of study-design, data recording and presentation format of outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
414
8
25

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 476 publications
(465 citation statements)
references
References 111 publications
(46 reference statements)
18
414
8
25
Order By: Relevance
“…Despite this technique, it has been reported that some bacteria remain inside the dentinal tubules, even after removal of the stained dentin [2][3][4] , and these remaining bacteria may subsequently lead to secondary caries 5) . Furthermore, it has been reported that the success rate of root canal treatment is about 80%, apparently due to incomplete intra-canal sterilization and obturation [6][7][8] . Hence, in order to obtain better results with caries and root canal treatment, it is necessary to invent new methods that can completely sterilize the infected dental tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this technique, it has been reported that some bacteria remain inside the dentinal tubules, even after removal of the stained dentin [2][3][4] , and these remaining bacteria may subsequently lead to secondary caries 5) . Furthermore, it has been reported that the success rate of root canal treatment is about 80%, apparently due to incomplete intra-canal sterilization and obturation [6][7][8] . Hence, in order to obtain better results with caries and root canal treatment, it is necessary to invent new methods that can completely sterilize the infected dental tissues.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 In terms of the insufficiency of the standard endodontic techniques in debridement and disinfection, long-term success may be unsustainable. 26,27,29,30,33 Reports demonstrate that long-term healing rates for these endodontic therapies are hindered in part due to the necessary removal of additional natural tooth structure for sufficient penetration of irrigants into the apical third of the root canal system. 33,34 The need for more progressive innovation to enhance debridement and disinfection has only grown as ongoing endodontic therapy inadequacies continue to present themselves.…”
Section: Jcdpmentioning
confidence: 99%
“…1,2 The success rate and associated factors of the tooth being treated are important to estimate the prognosis and provide sound evidence for treatment decisions. The concept of evidence-based treatment has gained increasing recognition in the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the preoperative presence versus absence of periapical radiolucency is a major indicator of postoperative healing or failure. [1][2][3][4][5][6][7][8][9][10] To assess the treatment outcome and elucidate the effect of specific factors on the outcome, randomized controlled trials are graded higher scores for the strength of level of evidence. 11 Treatment techniques and instruments have been effectively evaluated in randomized controlled studies.…”
Section: Introductionmentioning
confidence: 99%